2009
DOI: 10.1002/jsfa.3805
|View full text |Cite
|
Sign up to set email alerts
|

Feeding trials in organic food quality and health research

Abstract: Feeding experiments comparing organically and conventionally produced food are performed to assess the overall impact on the animals' health as a model for the effects experienced by the human consumers. These experiments are based on systems research and characterized by their focus on production methods, whole food testing and procedures in accordance with the terms of organic farming. A short review of such experiments shows that the majority of these tests revealed effects of the organically produced feed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 34 publications
0
35
0
1
Order By: Relevance
“…6,10 Few well-designed animal or human studies with clear health biomarkers looking at nutrition-related health effects have been performed. 1,18 No systematic nutrition-related health effects have been established either; however, some studies have shown that immunological parameters and growth might be sensitive to effects from cultivation systems. 14,21,22,42 Cultivation Methods Effect on Nutritional Quality and Health Biomarkers.…”
Section: ■ Discussionmentioning
confidence: 99%
“…6,10 Few well-designed animal or human studies with clear health biomarkers looking at nutrition-related health effects have been performed. 1,18 No systematic nutrition-related health effects have been established either; however, some studies have shown that immunological parameters and growth might be sensitive to effects from cultivation systems. 14,21,22,42 Cultivation Methods Effect on Nutritional Quality and Health Biomarkers.…”
Section: ■ Discussionmentioning
confidence: 99%
“…For example, the International Research Association for Organic Food Quality and Health aims to develop novel methods to study the effect of organic food on human health and has recently provided some useful guidelines on study design (28). Furthermore, ongoing work on animal models (29) may prove exceptionally helpful in providing insights for better targeted outcomes that may be relevant to human public health.…”
Section: Discussionmentioning
confidence: 99%
“…In different animal experiments, investigated effects of organic or conventional feed have mainly concerned two areas; fertility/reproduction and the immune system. Early studies, starting as early as 1926, investigated the outcome when organic fertilizers were compared with mineral, and found differences in growth rate (rats, two studies), pup survival rate (mice), reproduction (chicken), and fertility (bulls, rabbits), though three studies found no differences in growth rate or fertility [141]. Similarly, more recent studies have found differences on animals fed with organic versus conventionally grown feed, although in some studies no significant differences were observed.…”
Section: Health Biomarkers In Whole Organisms and In Vitro Studiesmentioning
confidence: 99%